Inferior Healing Rate in Isolated Meniscal Repair than that in Meniscal Repair with Concomitant ACL Reconstruction Evaluated with MRI - Isono M; Koga H; Nakagawa Y; Nakamura T; Sekiya I; Katagiri H (Malaysian Orthopaedic Journal, 2023)
Introduction: Isolated meniscal repair has been suggested as one of the contributing factors in unhealed meniscal repair. The purpose of this study was to compare the healing rate between isolated meniscal repair and meniscal repair with concomitant anterior cruciate ligament reconstruction (ACLR) using a standardised assessment method after propensity score matching. Materials and methods: Accuracy of the Crues' grading system for meniscal healing was validated using second-look arthroscopy as the reference standard in 17 patients. Propensity score matching (one-to-one) was performed between 26 patients who underwent isolated meniscal repair and 98 patients who underwent meniscal repair with concomitant ACLR. Patients were matched for sex, age, side and zone of the meniscal repair, and number of sutures. Healing rates at one year which were evaluated with magnetic resonance imaging (MRI) were compared between the two groups. Results: The sensitivity and specificity of the Crues' grading system on multiple plane MRI for meniscal healing were 100% and 83.3%, respectively. Both the isolated meniscal repair group and the meniscal repair with concomitant ACLR group included 21 patients after propensity score matching. Baseline characteristics did not differ significantly between the two groups. The healing rate was significantly lower in the isolated meniscal repairs group (14.3%) than in the meniscal repair concomitant with ACLR group (47.6%, P=0.04). Conclusion: The healing rate for isolated meniscal repair using a standardised MRI assessment method was inferior to that of meniscal repair with concomitant ACLR after propensity score matching.